Effects of electronic structure on the hydration of PbNO3+ and SrNO3+ ion pairs1. Issue 24 (28th June 2015) - Cooper, Richard J.; Heiles, Sven; Williams, Evan R.
<x xml:space="preserve">Abstract</x> Results from infrared photodissociation spectroscopy and theory show hydration of the ion pairs, PbNO3+ and SrNO3+, differ as a result of differences in electronic structure.